Transformational leadership : theory, research, and application to sports - Gomes, António Rui (2014)
Analyzing the influence of coaches on athlete performance and on the psychological experiences of team members (e.g., motivation, satisfaction, and cohesion) is a fascinating endeavor. Thus, it is not surprising that several authors have dedicated considerable effort to studying coaches’ mental representations and actions being proposed important conceptual models (Chelladurai, 1993; Côté, Salmela, Trudel, Baria, & Russell, 1995; Smoll & Smith, 1989; Jowett, 2007). Despite the unequivocal interest in these proposals, insufficient attention has been given to recent developments in leadership research, namely charismatic and transformational leadership (Bass, 1985; Burns, 1978; Conger & Kanungo, 1987; House, 1977). Therefore, analyzing the application of transformational leadership in sports contexts becomes important. Taking this need into consideration, this chapter aims to: (a) review the theoretical proposals and research conducted regarding charismatic/transformational leadership in several organizational contexts; (b) review the research conducted regarding transformational leadership in sports; and (c) propose conceptual, empirical, and practical guidelines concerning the application of transformational leadership in sports.